PSYCHOLOGICAL IMPORTANCE OF DEVELOPING THE PROFESSIONAL COMPETENCE OF TEACHERS - Akilova Kamola Sadulloevna (International Journal of Innovations in Engineering Research and Technology, 2021)
In this article, the role and advantages of psychology in the improvement of professional competence of teachers of Science in schools are discussed. It is also mentioned about the forms of professional Comets of teachers.